RELATIONSHIP BETWEEN THE TYPE OF LABOUR AND BREASTFEEDING ATTACHMENT (LATCH-ON) AND BREAST ENGORGEMENT INCIDENCE IN POSTPARTUM MOTHERS - Minta Rasi Marito; Tuti Asrianti Utami; Wilhelmus Susilo (Journal of Maternity Care and Reproductive Health, 2019)
Breast engorgement is one of the common problems that occur in the postpartum period. Inappropriate latch on would cause several problems including, baby's sucking uneffective, cracking nipple, breastmilk production is not maximal, and finally, the breast becomes engorgement. This study aimed to determine the relationship between the type of labor and breastfeeding latch-on and the breast engorgement incidence in the postpartum period. An observational study, the descriptive quantitative study, and cross-sectional approaches were applied, the study has been done from April to July 2018. Purposive sampling technique was used to select one hundred and two postpartum participants. The questioner, latch assessment tool, and assessment tool for observation were used in this study. The data were analyzed using chi-square, Kendall's tau b, and Kendall's tau c. The type of the delivery (p-value :0,001), and Breastfeeding attachment (p-value:0,001) had relationship with breast engorgement incidence in postpartum period. This study also showed that age (p-value:0,331), educational level ( p-value:0,532), and parity (p-valuee:0,056) were no relationship with breast engorgement incidence. It is expected from this study to increase the knowledge and independence of postpartum women about latch on to prevent breast engorgement. The future research would be able to study about mother's knowledge and motivation, family and health professional's support, postpartum stress, and early breastfeeding initiation in the surgery room.Keywords: Breast engorgement, latch on, types of delivery.